2014
DOI: 10.1007/s13595-014-0412-2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the potential spread of Fusarium circinatum, the causal agent of pitch canker in Europe

Abstract: International audienceContext Fusarium circinatum is an invasive forest pathogen causing pitch canker in Europe. It attacks several pine species and Douglas firs. It has already invaded a few places in the Iberian Peninsula and Italy. Aims The aim of this study is to develop a model for simulating the spread of F. circinatum once it enters Europe via various entry points such as harbours, border stations and from nurseries containing tree seedlings. Methods The spread rate was modelled as a function of the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…forests in Europe. Möykkynen et al [82] modeled the rate of spread of F. circinatum as a function of several factors, among which included host distribution and flight distance of insect vectors. Their model showed that because of the short distance at which spores are dispersed and the fragmentation of pine forests, unless there will be new introductions, the pathogen will most likely not spread to northern Europe.…”
Section: Connectivitymentioning
confidence: 99%
“…forests in Europe. Möykkynen et al [82] modeled the rate of spread of F. circinatum as a function of several factors, among which included host distribution and flight distance of insect vectors. Their model showed that because of the short distance at which spores are dispersed and the fragmentation of pine forests, unless there will be new introductions, the pathogen will most likely not spread to northern Europe.…”
Section: Connectivitymentioning
confidence: 99%
“…Sporadic outbreaks have been also reported in Italy and France (Carlucci, Colatruglio, & Frisullo, ; EFSA, ), but in both cases the pathogen has been officially eradicated (EPPO Global database, https://gd.eppo.int/). Although the probability of establishment of F. circinatum in Europe is high, considering the presence of susceptible hosts and the suitable climate conditions present in several countries (EFSA, ; Möykkynen, Capretti, & Pukkala, ; Watt, Ganley, Kriticos, & Manning, ), it is more likely that new outbreaks will be the result of new introductions, for example entry of contaminated material into zones where the pathogen is not yet present (Möykkynen et al, ; Santana, Coetzee, Wingfield, Wingfield, & Steenkamp, ). In contrast, it seems that the spread of spores, by the wind or insect vectors, is less efficient and less important than accidental introductions (Möykkynen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the probability of establishment of F. circinatum in Europe is high, considering the presence of susceptible hosts and the suitable climate conditions present in several countries (EFSA, ; Möykkynen, Capretti, & Pukkala, ; Watt, Ganley, Kriticos, & Manning, ), it is more likely that new outbreaks will be the result of new introductions, for example entry of contaminated material into zones where the pathogen is not yet present (Möykkynen et al, ; Santana, Coetzee, Wingfield, Wingfield, & Steenkamp, ). In contrast, it seems that the spread of spores, by the wind or insect vectors, is less efficient and less important than accidental introductions (Möykkynen et al, ). It has, however, been shown that F. circinatum inoculum may be dispersed by the wind over at least midrange distances, reaching in some cases up to 1,000 m (Dvořák, Janoš, Botella, Rotková, & Zas, ; Fourie et al, ; Garbelotto, Smith, & Schweigkofler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Its macro-and microconidia (asexual spores) are also spread by wind, water and insect vectors that infect trees through weather-related injures and wounds associated with insect feeding and pruning [20][21][22][23]. Understanding the temporal and spatial spore dispersal is, thus, critical for fine tuning efficient control measures that limit the disease expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not known how far the airborne spores may be dispersed [2], it was concluded that the conidia of F. circinatum have limited flight distance potential [2,23,24]. According to Garbelotto et al [24] its dispersal is little influenced by the wind direction and speed.…”
Section: Introductionmentioning
confidence: 99%